Opportunistic sampling to quantify plastics in the diet of unfledged Black Legged Kittiwakes (Rissa tridactyla), Northern Fulmars (Fulmarus glacialis) and Great Cormorants (Phalacrocorax carbo). Issue 2 (30th June 2017) - Acampora, Heidi; Newton, Stephen; O'Connor, Ian
Abstract: Seabirds can interact with marine litter, mainly by entanglement or ingestion. The ingestion of plastics can lead to starvation or physical damage to the digestive tract. For chicks, it could additionally lead to reduced growth, affecting survival and fledging. This study quantified the ingestion of plastics by seabird chicks via an opportunistic sampling strategy. When ringing is carried out at colonies, birds may spontaneously regurgitate their stomach contents due to the stress or as a defence mechanism. Regurgitates were collected from nestlings of three different species: Black-legged Kittiwake ( Rissa tridactyla, n = 38), Northern Fulmar ( Fulmarus glacialis, n = 14) and Great Cormorant ( Phalacrocorax carbo, n = 28). Plastic was present in all species, with the highest frequency of occurrence (FO) in Northern Fulmar chicks (28.6%), followed by Black-legged Kittiwakes (7.9%) and Great Cormorants (7.1%). The observed load of plastics on chicks, which have not yet left the nest, highlights the pervasive nature of plastic pollution. Highlights: Investigation of plastic ingestion in live seabird chicks First assessment of ingestion of plastics by seabird chicks in Ireland 11.3% of regurgitate samples (n = 80) contained plastic litter. All three examined species contained plastic litter.